1993
DOI: 10.1016/0266-7681(93)90208-w
|View full text |Cite
|
Sign up to set email alerts
|

Hand Infections: An Audit of 160 Infections Treated in an Accident and Emergency Department

Abstract: 160 consecutive hand infections presented to an Accident and Emergency department over a four-month period. All but one were treated solely on an out-patient basis. The mean delay to presentation was three days, the mean duration of treatment was six days. Follow-up to complete resolution was achieved in 89% of cases. No patients were treated with parenteral antibiotics. The need for careful assessment, early aggressive surgery, and meticulous attention to the principles of wound care by experienced clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
0
29
1
1
Order By: Relevance
“…Thus, the proportion of these conditions in this series of patients was higher than in the general population. However, results reported in studies from the United States [1,2,4,7] tally with the anatomic and socioeconomic parameters of the present study. We could find no data in previous studies to show how the time to operation of six hours in our series compares with that in other centers.…”
Section: Fig 4 Dorsal Digital Subcutaneous Abscesscontrasting
confidence: 62%
See 1 more Smart Citation
“…Thus, the proportion of these conditions in this series of patients was higher than in the general population. However, results reported in studies from the United States [1,2,4,7] tally with the anatomic and socioeconomic parameters of the present study. We could find no data in previous studies to show how the time to operation of six hours in our series compares with that in other centers.…”
Section: Fig 4 Dorsal Digital Subcutaneous Abscesscontrasting
confidence: 62%
“…Another paper that advocates outpatient management of the majority of hand infections likewise suggests a much higher number of patients seen during a short period of time (160 patients over four months) [4]. However, most authorities still advocate admission, elevation, immobilization, parenteral antibiotics, frequent observation, and surgical debridement/washout as the mainstays of management [7][8][9].…”
Section: Fig 4 Dorsal Digital Subcutaneous Abscessmentioning
confidence: 99%
“…Houshian et al and Stevenson and Anderson described Staphylococcus aureus as the sole cause of hand infections in 44% and 42% of patients, respectively. 11, 15 Dellinger et al and Stern et al alternatively reported an equally mixed organism culture of both Staphylococcus and Streptococcus species being most common, as it was present in 84% and 63% of patients, respectively. 14,16 Although not as common, a nearly limitless number of additional organisms have been identified in hand infections often associated with special circumstances such as diabetes, intravenous drug abuse, human or animal bites, occupational exposure, and sexual history.…”
mentioning
confidence: 96%
“…11 The most common mechanism of injury has been variably reported as human bites, surgical lacerations, and puncture wounds or splinters. 11,14,15 Numerous studies have characterized the most common pathogenic organisms in the hand as Staphylococcus aureus and beta-hemolytic streptococci, which thrive as human skin flora. Houshian et al and Stevenson and Anderson described Staphylococcus aureus as the sole cause of hand infections in 44% and 42% of patients, respectively.…”
mentioning
confidence: 99%
“…19 At this time, a resting volar splint can be used. Once acute signs of infection have settled physiotherapy is essential.…”
Section: Intravenous Antibioticsmentioning
confidence: 99%